Organizational justice and psychological employment contract breach: The mediating effect of trust - Saiful Azizi bin Ismail, Shakur Faruk, Zulkiflee bin Daud, (Opción, 2019)
This study examines the mediating effect of trust on the relationship between organizational justice and psychological employment contract breach in Nigeria public universities. The study is Cross-sectional in nature and data were collected from participants (lecturers) representing various public universities in Nigeria. The data was analyzed with Version 24 of Statistical Package for Social Sciences (SPSS) and the study revealed a negative and significant relationship between distributive justice and psychological employment contract breach unfulfilled promises. In conclusion, the trust did not mediate the relationship between distributive justice and psychological employment contract breach unfulfilled promises.